Differential expression of “A Disintegrin and Metalloproteinase 10” in hepatocellular carcinoma and the noncancerous hepatic tissues: Contribution to HCV-promoted hepatocarcinogenesis - Amal Abd El Hafez; Basem H. Elesawy; Heba S. E. I. Hany (Indian Journal of Pathology and Microbiology)
Background: A disintegrin and metalloproteinases (ADAMs) have emerged as therapeutic targets in many cancers. ADAM10 was particularly studied in hepatocellular carcinoma (HCC) for its potential role in hepatocarcinogenesis and HCC progression. Objective: To investigate the immunohistochemical (IHC) expression of ADAM10 in HCCs and the adjacent noncancerous tissues from 70 HCC patients, attempting to elucidate any association between ADAM10 and HCC development and/or progression. Materials and Methods: IHC staining for anti-ADAM10 was performed using horseradish peroxidase technique. An extent and intensity-dependent scoring was applied dividing samples into high- and low-expression groups. HCCs were statistically compared in relation with gender, age, cirrhosis, hepatitis C virus (HCV) status, alpha-fetoprotein (AFP) serum level, tumor size, multiplicity, encapsulation/invasion, grade, histological pattern and variant, mitosis, necrosis, vascular emboli, portal thrombosis, stage, recurrence, and mortality. Kaplan–Meier's method was used to analyze disease-free and overall survival (DFS and OS). Results: ADAM10 was expressed in 77.1% of HCCs compared with 42.9% of noncancerous tissues. Differential expression showed significant statistical difference (P = 0.02), as 38.6% of HCCs showed high expression, whereas 92.8% of noncancerous samples showed low expression. No significant differences were observed when high- and low-ADAM10 expression HCCs were compared with respect to all tested prognostic parameters except the HCV status. Patients whose tumors showed high-ADAM10 expression had relatively longer DFS and OS times, but with insignificant log-rank differences. Conclusions: ADAM10 is frequently expressed in HCCs compared with noncancerous hepatic tissues suggesting its role in hepatocarcinogenesis, especially in association with HCV. It has no association with HCC progression or survival. Further studies should be sought to investigate its validity as a therapeutic target.